Challenges to Delivering Home Parenteral Nutrition in Adult Patients With Limited English Proficiency. (25th September 2019) - Singh, Kevin; Bestgen, Ashley N.; Dugan, Ann; Singh, Amandeep; Kirby, Donald F.
Abstract: Failure to properly administer parenteral nutrition (PN) solutions can have deleterious effects on patients prescribed such therapies. The last few decades have seen diversification of the general population in the United States and elsewhere, with healthcare systems serving an increasing number of non‐English‐speaking patients and a more ethnically diverse population. Clinicians who provide care to this patient population encounter challenges in ensuring compliance and safe use of PN because of cultural and language barriers. Here we describe our experience of treating patients with limited English proficiency with respect to the barriers that prevent compliant and safe use of PN, especially in those discharged with home PN. We also describe the methods that we use to navigate these common issues to help clinicians provide the safest level of care to patients regardless of the patient's English proficiency.